A gentle reminder. Issue 3 (4th November 2014) - M. Watson, Ann
Abstract : Purpose: – This paper aims to address how utilizing positive psychology can be beneficial when academic libraries are faced with obstacles and challenges. Design/methodology/approach: – Opinion piece. Findings: – Personal observations. Originality/value: – Personal opinion and experience.